PELATIHAN PEMBUATAN KERIPIK SINGKONG DAN PEMANFAATAN SOSIAL MEDIA UNTUK PEMASARAN PRODUK INDUSTRI RUMAHAN PADA BUMDES DESA TERU - Rahmat Sulaiman; Ellya Hellmud; Harry Sudjikianto (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2021)
Around 57.9 million people in Indonesia who run UKM, only 9 percent use the internet seriously to sell their products, 37 percent use the basic internet and 36 percent haven't touched the internet at all. Selling online can also cut 71 percent of advertising costs that have been a large expenditure item for businesses. In the village of Teru, a village-owned enterprise (BUMDES) has been implemented to increase the productivity of activists in their village. The program has been run in 2018, but there are still some obstacles in running the program, such as packaging brands for products from activists that do not yet exist to the readiness of Human Resources in the use of internet technology in marketing their products. Following up on the problems at the BUMDES, the proposer would like to channel ideas in the form of community service to the village of Teru in overcoming and dealing with these problems, namely by developing plastic packaging technology and improving the quality of human resources in Teru village to face digital competition. Teru BUMDES is one that produces snacks. It is owned by residents of Teru, Simpang Katis District, Central Bangka, Bangka Belitung. The product of this activity is cassava chips. In addition to the use of practical packaging technology to attract consumers with attractive packaging, training is also conducted to improve the quality of existing human resources in Teru Village so that existing human resources are trained and can compete.